Effect of plasticizers and water on properties of HCFA geopolymers - Malkawi, A.B. (Trans Tech Publications Ltd, 2017)
In this study, different types of plasticizers were used to investigate their effects on the fresh and hardened properties of high calcium fly ash geopolymers (HCFA). Modified polycarboxylate polymers (G3) and lignin-based polymers (G1) were used as plasticizing admixtures and the results were compared to the effect of tap water addition. The results showed that all the admixtures used are effective in increasing the workability of the HCFA geopolymers mixtures and the workability increased by 25-48 compared to the control mixtures. However, the use of G3 has adversely affected the strength by a reduction of 20. While the use of G1 reduced the final setting time by 7 which is critical in the case of HCFA geopolymers where the final setting time occurs within 70 minutes. Water can be considered as the best admixture in terms of cost, setting time, and effect on compressive strength and it can be used where medium workability enhancement is required. © 2017 Trans Tech Publications, Switzerland.